PEMANFAATAN POJOK BACA SEBAGAI SARANA ALTERNATIF MENUMBUHKAN MINAT BACA PADA PEMBELAJARAN IPA SISWA SD - Nua, Marselina; Dinatha, Ngurah Mahendra; Dolo, Fransiskus Xaverius; Kua, Maria Yuliana (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This research aims to find out how the reading corner is used to foster students interest in reading in science learning at SDI Dhereisa. This research is a qualitative research with descriptive methods, aiming to see and determine the use of reading corners to foster students interest in reading in improving science learning at SDI Dhereisa. The targets of this research were all SDI Dhereisa. Students, from grade 1 to grade 6, with a total of 125 students. The problem that researchers found was the lack of students interest in reading in science learning which was still very low. The results of the research show that there has been an increase students interest in reading in science learning at SDI Dhereisa, this can be seen from the increasing number of students who spend time reading in the reading corner. Based on the increase in the number of students visiting the reading corner, it has been shown that having a reading corner can increase students interest in reading in science learning